2017
DOI: 10.3233/adr-170025
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Immunization with DNA for Alzheimer’s Disease in Animal Models: A Systematic Review from Literature

Abstract: Background:Alzheimer’s disease (AD) is a neurodegenerative disease that does not have a proven cure; however, one of the most promising strategies for its treatment has been DNA vaccines.Objective:The present review is aimed to report the new developments of the efficacy and safety of DNA vaccines for AD in animal models.Method:The method PRISMA was used for this review. The article search was made in the electronic databases PubMed, LILACS, and Scopus using the descriptors ‘’Alzheimer disease” and ‘’Vaccine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Intramuscular administration of saline causes scant inflammation, often comprised of scattered small aggregates of macrophages or other mononuclear inflammatory cells with or without individual myocyte degeneration or necrosis, edema, hemorrhage, and/or fibrosis (Figure 9). 2 Some antigens alone are highly immunogenic and may cause notable inflammation at the injection site, even when formulated without an adjuvant, although many have changes similar to those identified with saline administration.…”
Section: Microscopic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular administration of saline causes scant inflammation, often comprised of scattered small aggregates of macrophages or other mononuclear inflammatory cells with or without individual myocyte degeneration or necrosis, edema, hemorrhage, and/or fibrosis (Figure 9). 2 Some antigens alone are highly immunogenic and may cause notable inflammation at the injection site, even when formulated without an adjuvant, although many have changes similar to those identified with saline administration.…”
Section: Microscopic Findingsmentioning
confidence: 99%
“…Several therapeutic vaccines are currently being or have been investigated for potential treatment of a diverse number of diseases such as Alzheimer disease, Parkinson disease, and multiple types of cancer. [1][2][3] Vaccines are being developed using a wide variety of modalities, and formulations/therapies may include adjuvants or other immunological modulators to promote the desired immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The limited knowledge of the etiology of Alzheimer’s has rendered in vain numerous attempts hitherto pursued to find a resolutive treatment that is not simply limited to the alleviation of symptoms. Therefore, a worldwide effort is underway to discover the mechanisms responsible for the disease onset and progression and to find an efficacious therapy, developing either novel treatments [2,3,4] or preventive strategies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers are objective measures that can be used to indicate a patient's medical state accurately and reproducibly, and can be and often used to assess the risk of the patients [191]. We identified 40 unique biomarkers from 24 studies [110,114,155,[192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210]. Among these, 39 were found related to AD, 7 to vascular dementia, and 23 to other types of dementia.…”
Section: Ad/adrd Risk Factors In Rwd Literaturementioning
confidence: 99%
“…Among these, 39 were found related to AD, 7 to vascular dementia, and 23 to other types of dementia. Of the 24 studies, 26 biomarkers were found to indicate an increased risk of AD/ADRD [109,110,114,[192][193][194][195][196][197][198][199][200][204][205][206][207][208][209][210], 2 were associated with a decreased risk [155,203], and 2 showed inconsistent results [122,196]. The seven most studied biomarkers included tau, cholesterol, homocysteine, bone mineral density, magnesium, white matter hyperintensities, and vitamin D level.…”
Section: Ad/adrd Risk Factors In Rwd Literaturementioning
confidence: 99%